Mathematics learning for autism children / Nur Adillah Jeffery Sani - Jeffery Sani, Nur Adillah (2017)
Mathematics learning for autism children mobile application is application for autistic children from age 5 until 7 years old. The range of that children start to know numbers and learning basic mathematics operations such as addition and subtraction. Nowadays, our community have increase their awareness in education especially for these autistic children who sometimes left behind since they have communication and focusing in something problem. This application implement video modelling technique that may help students to enhance their learning skills. Besides, this application also made following the research that have made with cognitive skills. Therefore, this application may help them learn with least having any communication with other people.